Monitoring tumor burden by multicolor in vivo flow cytometry - Pitsillides, Costas; Kapnisis, Konstantinos; Anayiotos, Andreas (My University, 2013)
In vivo measurement of tumor burden, both in cancer research models and in patients, is an important parameter for the accurate assessment of disease progression and the response to therapeutic intervention [1]. Several in vivo imaging modalities have been utilized in the assessment of tumor burden, including functional magnetic resonance imaging, computer tomography and positron emission tomography [2, 3], fluorescence imaging [4, 5], intravital microscopy [6] and bioluminescence imaging [7]. More recently, the detection/quantification of circulating cancer cells has been explored as a method to evaluate tumor burden in the context of assessing disease stage, prognosis as well as monitoring disease progression following therapeutic intervention in cancer patients [8, 9]. Clinically, various ex vivo assays have been developed to detect cancer cells shed in circulation by primary tumors, including breast cancer, prostate cancer and small-cell lung cancer [10, 11]. In vivo flow cytometry has been developed as a method for real-time detection of circulating cancer cells injected into the circulation of experimental animals. The method does not require extraction of blood samples and is therefore well suited for long-term monitoring of circulating tumor cells. In this report, we report on the development of a multichannel in vivo flow cytometer to detect and quantify circulating cancer cells as a means of assessing the tumor burden in animal models.
Keywords: Vivo measurement; Tumor burden; Vivo flow cytometry; Multichannel in vivo flow cytometer